Computational thinking – Essential and pervasive toolset - Saari, Erni Marlina; Hopkins, Gail (Asian Journal of Assessment in Teaching and Learning, 2020)
Education 21st century is all about enfolding digital technology. The theme “Higher Education 4.0: Knowledge, Industry and Humanity”, mandated from Malaysia’s former Higher Education Minister Datuk Idris Jusoh. The minister identified that universities have to be trained to adapt and change the curriculum so that graduates are capable to fill in jobs which are yet to arise.  This Fourth Industrial Revolution 4.0 as part of the call to revamp the Malaysia higher education system. There are nine Malaysia future-proof skills that has been listed under Ministry of Higher Education module on Framing Malaysian Higher Education 4.0 – future-proof talents. There are creativity and innovation; Holistic Entrepreneurial and Balanced; Resilience; leadership; Compassion and mindfulness; values and ethics; flexibility and adaptability; critical thinking and problem solving and finally communication and language proficiency. The above mentioned points are future-proof skills sets for Malaysian graduates. There are three additional future-proof attributes which are lifelong learners, multiple intelligence and competencies and computational thinking. This qualitative study explored the significant area in the recent digital technology and development hence, it will be one of the crucial knowledge that should be acquired by everyone and anyone not only in Malaysia but in the whole wide world. Technology is moving rapidly and educators have to keep up with this fast pace. This issue attentively allied with the terminology pioneered by Jeanette Wing that is called computational thinking (CT). The interviewed is carried out among eleven Malaysian pre-service teachers and existing teachers under PGCE (Post Graduate Certificate in Education) program in the United Kingdom, to study on their attitudes towards the idea of learning programming. Through the interviews, the researcher was able to record and interpret trainee teachers’ perceptions of the motivation to learn programming. The data were then analysed and categorised before the final codes were determined to get the final output using thematic code analysis technique. The findings show that learning programming is possible for those who had no computing background thus answered one of the aim of this study that CT skills could be adopted in any fields and more creators or designers will be established compared to the passive users. There was a rational consideration of the value of learning programming to their professional skills and the studies have asked whether understanding such will raise the participants’ engagement with learning a programming language and thus assist them to acquire CT skill.